Effects of atmospheric-thermosonication process on phenolic compounds extraction, extraction productivity and antioxidant activity of freeze-dried green tea and green coffee aqueous extracts - Karim Moradi Kashksara; Hamid Tavakolipour; Mohsen Mokhtarian (Journal of Agriculture and Food Research, 2023)
The atmospheric-thermosonication extraction (ATSE) of bioactive compounds from freeze-dried aqueous extract of green tea (FDGT) and green coffee (FDGC) herbal plants was performed to improve the separation of phenolic compounds. The extraction process was optimized by considering the operating conditions of temperature (25–85 °C), extraction time (15–35 min) and the amplitude of ultrasonic waves (0–100%) to achieve freeze-dried herbal extracts (FDHEs). According to Pearson correlation statistics approach, strong and negative correlation was observed between two main quantitative indicators of (EC50 and TPC) for FDGT (r = −0.9717 & R2 = 0.944) and FDGC (r = −1.00 & R2 = 1.00), respectively. While the extraction productivity ratio (TPC/EC50) of FDGT and FDGC under conventional extraction (maceration extraction technique) was significantly increased to ∼24.61 and ∼76.60 respectively, the noted parameter increased at rates of ∼34.19 and ∼88.64 after applying ATSE treatment at the similar conditions. Additionally, the caffeine content of FDGT was ∼50% more than FDGC. Overall, ultrasound-assisted extraction of phenolic antioxidants from herbal plants used much less energy than those extracted with conventional method and obtained extracts had a higher quality and inhibiting components against pathogenic microorganism than those extracted with commercial method due to extraction at lower temperatures.